Enhancing Electrocatalytic Activity for Hydrogen Evolution by Strongly Coupled Molybdenum Nitride@Nitrogen-Doped Carbon Porous Nano-Octahedrons - Zhu, Y.; Chen, G.; Xu, X.; Yang, G.; Liu, M.; Shao, Zongping (American Chemical Society, 2017)
Developing highly efficient and affordable noble-metal-free catalysts toward the hydrogen evolution reaction (HER) is an important step toward the economical production of hydrogen. As a nonprecious-metal catalyst for the HER, molybdenum nitride (MoN) has excellent corrosion resistance and high electrical conductivity, but its catalytic activity is still inadequate. Here we report our findings in dramatically enhancing the HER activity of MoN by creating porous MoN@nitrogen-doped carbon (MoN-NC) nano-octahedrons derived from metal–organic frameworks (MOFs). The composite catalyst displays remarkably high catalytic activity, demonstrating a low overpotential of 62 mV at a current density of 10 mA cm–2 (η10), a small Tafel slope of 54 mV dec–1, and a large exchange current density of 0.778 mA cm–2 while maintaining good stability. The enhancement in catalytic properties is attributed to the unique nanostructure of the MoN, the high porosity of the electrode, and the synergistic effect between the MoN and the nitrogen-doped carbon substrate. The performances are among the best ever reported for nonprecious-metal-based electrocatalysts (comparable to those of a 20% Pt/C commercial catalyst), making the porous MoN-NC nano-octahedrons some of the most active and acid-stable electrocatalysts for the HER.